PENGARUH INDEPENDENSI, PENGALAMAN, PROFESIONALISME DAN AKUNTABILITAS TERHADAP KUALITAS AUDIT - Nanan Sunandar (Nusa Putra University, 2019)
This research aims to empirically examine the effect of independence, experience, professionalism, and accountability on audit quality. Respondents used in this study are external auditors or independent auditors working in the Public Accountant Firm. Data collection was carried out through questionnaires which were delivered directly to respondents. 60 questionnaires have been returned and declared valid to be processed, which have been submitted. Data processing using multiple linear regression models with SPSS software version 20.0. The results of this study indicate that independence and professionalism affect audit quality.